PEMANFAATAN LIMBAH KULIT SISA PRAKTIKUM DALAM PEMBUATAN BUCKET HAT - Gilang A S K Ningtyas (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2025)
Workshops or laboratories in educational units are among the producers of waste that can cause environmental problems if not managed properly. One of the duties of a Laboratory Technician (PLP) is to ensure that laboratory waste management is carried out effectively and sustainably. In practical activities involving leather testing conducted by students, waste is generated in the form of leather scraps and rejected leather, which falls under the category of practicum waste. This waste needs to be recycled through a series of treatments so it can be repurposed as material for fashion products, specifically bucket hats. The creation of the bucket hat as a result of recycling practicum leather waste is carried out using a creation method based on the Design Thinking concept, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. The process of making the bucket hat includes both manual work and machine use. This research produced a bucket hat product titled "Roboard Hat," a futuristic-style hat made from leather waste material with added used keyboard accents. The study concludes that waste generated from practicum activities can be repurposed into a fashion product with artistic value.